Modeling and analysis of eddy current losses in permanent magnet machines with multi-stranded bundle conductors - Arumugam, Puvaneswaran; Dusek, Jiri; Mezani, Smail; Hamiti, Tahar; Gerada, C. (Elsevier, 2015)
This paper investigates the influence of eddy current losses in multi-stranded bundle conductors employed in out-runner permanent magnet machines, by adopting an analytical model. The analytical model is based on a sub-domain field model that solves the two-dimensional magnetostatic problem using the separation of variables technique for each of the non-magnetically permeable machine sub-domains: PM, airgap and slots. The validity and accuracy of the proposed model is verified using finite element analysis and then used to investigate the eddy current losses. The machine considered for the analysis has 36 slots and 42-poles previously designed for aircraft taxiing. The influence of the number of turns and the conductor cross-sectional area are investigated. It is shown that efficiency can be improved considerably by the choice of multi- stranded bundle conductors.